Tupo ja media Talous- ja työmarkkinapoliittisen julkisuuden toimintahorisontit kolmella vuosikymmenellä - Reunanen, Esa (Tampere University Press, 2020)
This book explores the media coverage of three prominent Finnish labor market cases in the newspaper Helsingin Sanomat. It analyzes how this arena supported or undermined the power positions of each side and the reaching of the contract. The cases in study are the first proper general agreement in 1968 (Liinamaa 1) and the endeavors for so-called "social contract" by the Government of Esko Aho (1991) and Juha Sipilä (2015). The study identifies changes and continuities in the political discourses, in the ways of making validity claims in political argumentation, and in media/journalistic interventionism. These content analytical viewpoints illustrate the theoretical ideas about mediatization of politics presented in the book. By analyzing corporatist and pluralist aspects of decision making, the book opens a view in the relationships among labor market organizations, the Government, and the media in the three decades studied.